What is the core essence of small city boutique hotels? - Loureiro, Sandra Maria Correira (2020)
Loureiro, S. M. C., Rita, P., & Sarmento, E. M. (2020). What is the core essence of small city boutique hotels? International Journal of Culture, Tourism, and Hospitality Research, 14(1). https://doi.org/10.1108/IJCTHR-01-2019-0007